Measurements of volatile organic compounds by GC-MS and radon by dual-flow loop detector at Lucas Heights, New South Wales, February-June 2019 - Jhonathan Ramirez-Gamboa; Clare Paton-Walsh; Ian Galbally; Jack B Simmons; Elise-Andrée Guérette; Alan D Griffiths; Scott D Chambers; Alastair G Williams; Leisa Dyer (PANGAEA, 2022)
Measurements of selected volatile organic compounds were made using a 7890B Agilent Technologies Gas Chromatograph equipped with an HP-5 MS column (30 m exttimes 0.25μm exttimes 0.25 mm ID; Agilent Technologies, Santa Clara, CA, USA), coupled to a single quadrupole electron ionisation mass spectrometer (Agilent 5977B with Xtr EI source, Agilent Technologies, Santa Clara, CA, USA). The mass spectrum detector was operated in selected ion mode (SIM). 30-minute measurements were made quasi-continuously throughout the campaign, though large gaps exist in the measurement timeseries corresponding to instrument malfunction and maintenance periods. Measurements we made on the campus of the Australian Nuclear Science and Technology Organisation (ANSTO) at Lucas Heights, New South Wales (34°03' 09.4'' S 150°59' 08.2'' E). Sampled air was drawn from a PTFE sampling inlet 7.5 m above ground level. Radon measurements were also made on the ANSTO campus. Continuous hourly measurements were made at 2 m above ground level using a 1500 L two-filter dual-flow-loop radon detector designed and built at ANSTO. Meteorological measurements reported here were made approximately 500 m distant from the sampling site of other variables from sensors 10 m above ground level. Meteorological measurements were made by ANSTO staff and were provided by Leisa Dyer, Senior Atmospheric Scientist at ANSTO. Further instrumental, sampling and analytical details are provided in the publication associated with these data (Ramirez-Gamboa et al., 2020).